Long term antifungal efficacy of silver-zinc zeolite nanoparticles incorporated in two soft denture liners - An in vitro assessment - Amanda Nadia Ferreira; Kathleen D'Souza; Meena Aras; Vidya Chitre; Shobha Parsekar; Maria Jose Wiseman Pinto (Wolters Kluwer Medknow Publications, 2022)
Background: There is generally a lack of compliance in patients who report with oral candidiasis, as they are advised to temporarily stop wearing the prosthesis and are prescribed topical antifungals which are generally unpleasant to taste and follow a rigorous schedule. Furthermore, with the alarming evidence of drug resistance, there is a need for an enhanced drug and drug delivery system. The aim of the study was to determine the dose-dependent antifungal efficacy of silver-zinc zeolite nanoparticles (SZZ-NPs) when incorporated in two brands of soft denture liners against Candida albicans. Materials and Methods: A total of 72 samples were made to determine the in vitro antifungal efficacy of SZZ-NPs and fluconazole by measuring the mean inhibition diameter (MID). Two concentrations of SZZ-NPs were compared (0.5%, 2% w/w) with fluconazole 5%w/w which is routinely prescribed. The antifungals were incorporated in two types of commercially available soft denture liners (Visco gel, GC soft denture liner). The MIDs were measured at day 1, day 7, day 15, and day 30. The values obtained (P < 0.001) were analyzed with one-way ANOVA, Tukey's post hoc, and independent t-test. Results: A statistically significant difference (P < 0.001) was noted among all the antifungal agents at all the time intervals tested. The anti-fungal efficacy of SSZ-NPs 2% w/w incorporated in GC soft denture liner was significantly superior (P < 0.001) to all groups tested and it retained its antifungal efficacy even on day 30 (MID: 18.33 ± 2.44). Conclusion: SZZ-NPs 0.5%w/w, 2%w/w, and fluconazole 5%w/w can be incorporated with soft denture liners against C. albicans. Fluconazole 5%w/w is the recommended choice for short-term antifungal efficacy, while SZZ-NPs 2%w/w is recommended when long-term antifungal efficacy is needed. GC soft denture liner was the recommended choice.